Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1109/tbme.2010.2093133
|View full text |Cite
|
Sign up to set email alerts
|

Toward Unsupervised Adaptation of LDA for Brain–Computer Interfaces

Abstract: There is a step of significant difficulty experienced by brain-computer interface (BCI) users when going from the calibration recording to the feedback application. This effect has been previously studied and a supervised adaptation solution has been proposed. In this paper, we suggest a simple unsupervised adaptation method of the linear discriminant analysis (LDA) classifier that effectively solves this problem by counteracting the harmful effect of nonclass-related nonstationarities in electroencephalograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
272
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(276 citation statements)
references
References 24 publications
3
272
0
1
Order By: Relevance
“…In this context, several asynchronous approaches have resulted in supervised and non-supervised learning techniques to cope with the changes in the distributions due to sessionand user-related non-stationarities [5], [7], [8]. In a similar way, past studies with synchronous signals have found userrelated differences in the averaged P300 ERP component from the neurophysiological point of view [6].…”
Section: Introductionmentioning
confidence: 93%
“…In this context, several asynchronous approaches have resulted in supervised and non-supervised learning techniques to cope with the changes in the distributions due to sessionand user-related non-stationarities [5], [7], [8]. In a similar way, past studies with synchronous signals have found userrelated differences in the averaged P300 ERP component from the neurophysiological point of view [6].…”
Section: Introductionmentioning
confidence: 93%
“…The bias b = w Tμ can be calculated without class information based on the estimated pooled meanμ = (μ 1 +μ 2 ) /2, if both classes can assumed to the equally sized (see [9]). …”
Section: Ldamentioning
confidence: 99%
“…The bias of the LDA in (2) was adapted by updating the pooled meanμ after each trial. For more information on LDA unsupervised adaptation see [9].…”
Section: F Runs 5: Unsupervisedmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem arises of a variety of applications, such as computer vision [6][7][8][9], multivariate time series [10], and sentiment analysis [11,12]. In this paper, an invariant latent space is extracted to tackle domain shift problem.…”
Section: Introductionmentioning
confidence: 99%